Fitrah manusia: Analisis terhadap novel ayat-ayat cinta 2 karya Habiburrahman El-Shirazy - Rosmah Derak (Unisza, 2024)
Habiburahman El-Shirazy is an Indonesian novelist who writes novels with Islamic messages. Among his noteworthy works are Ayat-Ayat Cinta, Ketika Cinta Bertasbih 1, Ketika Cinta Bertasbih 2, Pudarnya Pesona Cleopatra, Di Atas Sajadah Cinta, Dalam Mihrab Cinta, Cinta Suci Zahrana, Ayat-Ayat Cinta 2, Bumi Cinta dan Api Tauhid. This research will examine one of his novels, ‘Ayat-Ayat Cinta 2’, using a method to study works based on Islam known as a fitrah criticism of Sohaimi Abdul Aziz's views. Employing a textual analysis, the study focuses on the author-created characters and characterizations. The study indicates that the moral character pattern dominates the entire narrative when the author emphasizes human nature that tends towards goodness and nobility. It was also demonstrated that the human nature that possesses Asmaul Husna’s attributes can manifest them in themselves. The core pattern of religion, which is to recognize God’s uniqueness, may be noticed in the characters’ Islamic faith beliefs. Several characters return to the fitrah of a Muslim, demonstrating the probable Islamic, holy, and safe aspect of fitrah, as understood by fitrah's critics. The pattern of fitrah connected with worship also suggests that the featured characters are aware of their nature that was created to worship God. The findings of the analysis indicate that the author has successfully employed three patterns in Islamic teachings, namely belief, worship, and morals, to develop a character who adheres to the Islamic faith and can serve as a role model for the readers to be good believers.